Food-web interactions in a coastal ecosystem influenced by upwelling and terrestrial runoff off North-West Spain. (May 2020) - Giralt Paradell, Oriol; Díaz López, Bruno; Methion, Séverine; Rogan, Emer
Abstract: Ecopath with Ecosim has been used to create mass-balance models of different type of ecosystems around the world to explore and analyse their functioning and structure. This modelling framework has become a key tool in the ecosystem approach to fisheries management, by providing a more comprehensive and holistic understanding of the interactions between the different species. Additionally, Ecopath with Ecosim has provided a useful framework to study ecosystem maturity, changes in the ecosystem functioning over time and the impact of fisheries and aquaculture on the ecosystem, among other aspects. The present work explores the ecosystem functioning and structure in an anthropogenically impacted coastal area, influenced by seasonal coastal upwelling and high input of nutrients from rias (ancient drowned tectonic valleys) off North-West Spain. A mass-balance model with 23 functional groups was created using Ecopath to study the trophic interactions in the ecosystem during the post-upwelling period (August to October) in 2017. The model described an immature, wasp-waist ecosystem, that shared characteristics of ecosystems found in upwelling areas and ecosystems found in fjords or coastal embayments. Deeper analyses highlighted the importance of small planktivorous pelagic fish as a keystone functional group, and of zooplankton, blue whiting ( Micromesistius poutassou ) and phytoplankton as structuring groups in the ecosystem. Additionally, the study revealed that the existing fishing pressure on species of intermediate-high trophic levels could alter ecosystem functioning and structure, and ultimately affect top predators in the area. Findings of this study provide baseline information in ecosystem functioning and structure in the area and highlight the need to deeper study the effects of fisheries and their potential impacts on top predators. Highlights: A mass-balance model of a human impacted coastal ecosystem off NW Spain was created. Ecopath described a relatively immature ecosystem with wasp-waist control. This ecosystem had characteristics of upwelling areas fjords and coastal embayments. Key fish species highlight the vulnerability of the ecosystem to intense fishing.